Impact of early and late age-related macular degeneration on vision-specific functioning. Issue 5 (17th October 2010) - Lamoureux, Ecosse L; Mitchell, Paul; Rees, Gwyn; Cheung, Gemmy; Yeo, Ian; Lee, Shu Yen; Liu, Erica; Wong, Tien Y
Abstract : Aim: To assess the impact of early and late age-related macular degeneration (AMD) on vision-specific functioning in Singapore Malays. Methods: AMD was assessed from fundus photographs. The following endpoints were considered for (a) AMD: no AMD, early AMD, and late AMD; (b) drusen: absence and presence; and (c) retinal pigment epithelium (RPE) abnormality: absence and presence. Vision functioning was assessed using the modified VF-11 scale validated using the Rasch analysis. The overall functioning score was used as the main outcome measure. Results: Retinal photographs and vision functioning data were available only for 3252 participants. After age standardisation, the prevalence of early AMD was 3.5% and late AMD 0.34%. In multivariate models, after adjusting for age, gender, education, level of income, smoking status, ocular condition and hypertension, only late AMD was independently associated with poorer vision functioning when compared with no AMD or early AMD (β (β regression coefficient)=−6.4 (CI −11.7 to −2.1; p=0.01)). Early AMD or its principal components, drusen or RPE abnormality, were not independently associated with vision functioning (p>0.05). In adjusted multinomial logistic regression models, people with late AMD were twice as likely (OR=2.23; 95% CI 1.16 to 7.11) to have low overall functioning than those without AMD. Conclusions: Late AMD has a significant impact on visual functioning, but early AMD, drusen and RPE changes have no impact. These data highlight the importance of preventive public health strategies targeting patients with early AMD signs in order to prevent progression to late AMD when visual function is compromised.